Enhancing lecture comprehension in English medium of instruction: a case study of an international business management programme in Belgium - Kremer, Marcelo; Valcke, Martin (Journal of Management and Business Education, 2024)
The growing global trend of adopting English as a Medium of Instruction (EMI) in higher education, particularly in non-English-speaking countries, presents a unique set of challenges. This study focuses on a group of students in Belgium navigating EMI within the context of a bachelor’s degree programme in International Business Management. It delves into the strategies employed by both lecturers and students to enhance learning outcomes while listening to EMI lectures. Through classroom observations and focus groups with EMI students, this research uncovers valuable insights into effective teaching and strategies that can be instrumental in ensuring EMI does not hinder the achievement of educational objectives. The study's findings contribute by putting forward a comprehensive repertoire of didactic strategies and resources, offering valuable guidance to lecturers, students, and curriculum developers involved in the EMI landscape of higher education, with a particular emphasis on improving students' comprehension of lecture content.